Analysis of the Impact of Covid-19 and Company Policies on Sales Volume in the New Normal Period (Case Study: Medan Market Center) - Yennuar Pratama, Jeslyn; Irvan Rolyesh Situmorang (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2022)
At this time, Small Micro Enterprises both in the service and production business sectors are experiencing many severe challenges during the covid-19 pandemic. The things that are most felt by Micro, Small Enterprises are a significant decrease in turnover, lack of customers, difficulty getting profits, and inhibition of product sales due to social distancing and Large-Scale Social Restrictions (PSBB) that apply throughout city Indonesia. So this study was conducted to determine the influence of the impact of the Covid-19 pandemic and company policies on sales volume in the Medan Market Center. The research method uses a quantitative approach by taking data in a survey of sellers at the Medan Market Center. In this study, the source of data obtained is the primary data source. A total of 88 respondens taken will fill out the questionnaire. This research shows that the company's policy is a product price strategy that affects sales volume at the Medan Market Center.